Case Report: Supernormal Vascular Aging in Leningrad Siege Survivors - Rotar, Oxana; Boyarinova, Maria; Moguchaya, Ekaterina; Tolkunova, Kristina; Kolosov, Nikita; Rezapova, Valeriia; Freylikhman, Olga; Usoltsev, Dmitrii; Melnik, Olesya; Sergushichev, Alexey; Solntsev, Vladislav; Kostareva, Anna; et al. (Frontiers in Cardiovascular Medicine, 2022)
Age-related changes in the vascular system play an important role in the biological age and lifespan of a person and may be affected from an early age onwards. One of the indicators of changes in the vascular system is arterial wall stiffness and its main measure - carotid-femoral pulse wave velocity. We examined arterial wall stiffness in a sample of 305 siege Leningrad survivors to assess how hunger and stressful conditions during fetal development and early childhood affected the state of the cardiovascular system at later age and what factors may neutralize the negative impact sustained in early childhood. Here we present an evaluation of two unique patients with supernormal vascular aging phenotype from this cohort and describe the details of congruence between hereditary resistance and practiced lifestyle yielding slower biological aging rate.